PENGEMBANGAN MEDIA INTERAKTIF FLIPBOOK MAKER UNTUK PEMBELAJARAN MATEMATIKA ANAK USIA DINI DI RA BAHRUL ULUM SAWAHAN TUREN-MALANG - Yulia, Nikmahtul Khoir Tri; Rahayu, Titin (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2025)
The development of technology will always transform every year such as AI (Artificial Intelligence) based technology. The purpose of this study is to describe the concept of interactive flipbook maker media, cognitive learning through interactive flipbook maker media, and the results of flipbook maker development. The research method used is research and development (RnD), researchers create a work that produces products and has usefulness and production value according to the RnD stage. Data collection techniques use observation, data instruments, and documentation. The results of the study are findings about interactive media design made using the flipbook maker Pro V4.3.4.0 application. The mapping of cognitive themes contained in the product includes counting, one-to-one correspondence, number comparison, and recognizing and writing numbers. The validated development results reached 96.25% in product design. In the mapping of cognitive material contained in the product, the validation results reached 97.5%. The results of the responsive validation carried out during two product trials on students reached 41% to 59% of the small group. Meanwhile, the results of the product development response reached 42% to 58% of the large group. Based on the research analysis, it can be concluded that the flipbook maker product is declared quite feasible. The scope of product revision based on the validity test, the value that has been produced has reached above 50%, which means that the flipbook maker product can be produced in large quantities and can be used as an alternative digital and movable learning media so that children can use this media in learning activities wherever and whenever.